Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.chemmater.6b03676
|View full text |Cite
|
Sign up to set email alerts
|

Switch of Surface Adhesion to Cohesion by Dopa-Fe3+ Complexation, in Response to Microenvironment at the Mussel Plaque/Substrate Interface

Abstract: Although Dopa-Fe 3+ complexation is known to play an important role in mussel adhesion for providing mechanical properties, its function at the plaque/substrate interface, where actual surface adhesion occurs, remains unknown, with regard to interfacial mussel adhesive proteins (MAPs) type 3 fast variant (fp-3F) and type 5 (fp-5). Here, we confirmed Dopa-Fe 3+ complexation of interfacial MAPs and investigated the effects of Dopa-Fe 3+ complexation regarding both surface adhesion and cohesion. The force measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 42 publications
1
70
0
Order By: Relevance
“…The concomitant increase of scattering peaks for TA ( Figure 1c) is likely a result of the stabilization effect of phenolic ring by metal ion coordination and similar phenomena have been observed in previous studies. 27,28 In addition, XPS measurement can only detect the presence of iron in the ELSC after placing in saltwater (a 3.5 wt% NaCl solution) for 100 days, implying the minor amounts of iron (Supporting Information Figure S2). Fe 2p3/2 and Fe 2p1/2 signals are observed at around 711 and 725 eV, respectively, with a 2p peak separation of 14 eV, suggestive of the presence of Fe 3+ .…”
Section: A Dynamic and Continuous Iron Sequestration Systemmentioning
confidence: 99%
“…The concomitant increase of scattering peaks for TA ( Figure 1c) is likely a result of the stabilization effect of phenolic ring by metal ion coordination and similar phenomena have been observed in previous studies. 27,28 In addition, XPS measurement can only detect the presence of iron in the ELSC after placing in saltwater (a 3.5 wt% NaCl solution) for 100 days, implying the minor amounts of iron (Supporting Information Figure S2). Fe 2p3/2 and Fe 2p1/2 signals are observed at around 711 and 725 eV, respectively, with a 2p peak separation of 14 eV, suggestive of the presence of Fe 3+ .…”
Section: A Dynamic and Continuous Iron Sequestration Systemmentioning
confidence: 99%
“…Therefore, the freshly formed hydrogel with uniformly distributed Ppy could be directly administered in vivo. Second, the Fe 3+ could form mono‐ or bis‐catechol‐Fe 3+ complexes with the dopamine groups in HPAE–Py polymer at neutral pH . The adhesion‐predominant catechol–Fe 3+ complexation could thus enhance the wet adhesion of the hydrogels.…”
mentioning
confidence: 99%
“…[140] Such works include AFM studies, [157] binding of DOPA-containing mfps [158] and hydrolysed peptides, [ 159 ] spectroscopic and chemical characterization of the complexes formed during cross-linking [160] and metal-mediated cross-linking in mfps. [161] In a recent study, Cha et al [162] confirmed DOPA-Fe(III) complexation in mfp-3F and mfp-5 and investigated its effect on both cohesion and surface adhesion (Figure 13). At low pH values (similar to those of the local acidic environments during the secretion of adhesive proteins), DOPA-Fe(III) complexation decreases.…”
Section: Reviewmentioning
confidence: 99%